Perfect - Hopkins, Ellen (New York : Margaret K. McElderry Books, 2011)
Nevada teenagers Cara, Kendra, Sean, and Andre, tell in their own voices of their very different paths toward perfection and how their goals change when tragedy strikes.
Companion to Impulse.
HL 570
Keywords: Self-esteem -- Juvenile fiction; Perfectionism (Personality trait) -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Families -- Nevada -- Juvenile fiction; Nevada -- Juvenile fiction; Novels in verse